Effect of Administration of Azithromycin and/or Probiotic Bacteria on Bones of Estrogen-Deficient Rats - Urszula Cegieła; Piotr Londzin; Aleksandra Janas; Maria Pytlik; Joanna Folwarczna (MDPI AG, 2022)
The gut microbiota plays an important role in maintaining homeostasis, including that of the skeletal system. Antibiotics may affect the skeletal system directly or indirectly by influencing the microbiota. Probiotic bacteria have been reported to favorably affect bones in conditions of estrogen deficiency. The aim of this study was to investigate the effects of azithromycin (AZM) administered alone or with probiotic bacteria (Lactobacillus rhamnosus; LR) on bones in estrogen-deficient rats. The experiments were carried out on mature rats divided into five groups: non-ovariectomized (NOVX) control rats, ovariectomized (OVX) control rats, and OVX rats treated with: LR, AZM, or AZM with LR. The drugs were administered for 4 weeks. Serum biochemical parameters, bone mineralization, histomorphometric parameters, and mechanical properties were examined. Estrogen deficiency increased bone turnover and worsened cancellous bone microarchitecture and mechanical properties. The administration of LR or AZM slightly favorably affected some skeletal parameters of estrogen-deficient rats. The administration of AZM with LR did not lead to the addition of the effects observed for the separate treatments, indicating that the effects could be microbiota-mediated.